Analisis Faktor Yang Memengaruhi Kepuasan Kerja Perawat Di RSUD dr. Pirngadi Medan - Albert Jeo; Arifah Devi Fitriani; Masnelly Lubis (CV. Pusdikra Mitra Jaya, 2023)
The establishment of the ASEAN Economic Community (AEC) in 2015 allows a country to sell health services including nurses to ASEAN countries, this is a threat for nurses in Indonesia because they have to be able to compete with nurses from other countries. Indonesian nurses still have to make improvements both in terms of competence and quality of service where to be able to improve the quality of service, nurses in carrying out their duties must get job satisfaction. Job satisfaction is a positive attitude towards work in a person which is individual. Each individual has a different level of job satisfaction in accordance with the value system that applies to the person where many factors can affect job satisfaction. This study aims to analyze the factors that affect job satisfaction (compensation, promotion opportunities, supervision, coworkers, job characteristics, work environment) of nurses at RSUD Dr. Pirngadi Medan. The research design was observational study with cross-sectional approach and using questionnaires as a research instrument. The sample was 79 State Civil Apparatus Nurses. The statistical test used is the chi-square test and logistic regression. The result shown that 57% of nurses who were satisfied with their jobs as many as 40.5% stated that compensation was in the unfavorable category, 45.6% stated that promotion opportunities were in the sufficient category, 34.2% stated that supervision in the favorable category, as many as 35.5% stated that coworkers were in the unfavorable category, as many as 37.1% stated that the characteristics of work in the appropriate category and as many as 30.5% stated the work environment was in the good category. Multivariate test analysis results using logistic regression showed that compensation, promotion opportunities, supervision, coworkers, job characteristics, and work environment has a value of p<0,05 which means significantly influence job satisfaction. The conclusions was obtained that compensation is the most dominant factor affecting job satisfaction of nurses in RSUD Dr. Pirngadi Medan. The hospital management is expected to pay more attention to the factors of job satisfaction of nurses in order to improve the quality of service at the hospital.